Extracorporeal membrane oxygenation support for life-threatening acute severe status asthmaticus. (March 2017) - Di Lascio, Gabriella; Prifti, Edvin; Messai, Elmi; Peris, Adriano; Harmelin, Guy; Xhaxho, Roland; Fico, Albana; Sani, Guido; Bonacchi, Massimo
Introduction: Status asthmaticus is a life-threatening condition characterized by progressive respiratory failure due to asthma that is unresponsive to standard therapeutic measures. We used extracorporeal membrane oxygenation (ECMO) to treat patients with near-fatal status asthamticus who did not respond to aggressive medical therapies and mechanical ventilation under controlled permissive hypercapnia. Materials and methods: Between January 2011 and October 2015, we treated 16 adult patients with status asthmaticus (8 women, 8 men, mean age: 50.5±10.6years) with veno-venous ECMO (13 patients) or veno-arterial (3 patients). Patients failed to respond to conventional therapies despite receiving the most aggressive therapies, including maximal medical treatments, mechanical ventilation under controlled permissive hypercapnia and general anesthetics. Results: Mean time spent on ECMO was 300±11.8 hours (range 36–384 hours). PaO2, PaCO2 and pH showed significant improvement promptly after ECMO initiation p=0.014, 0.001 and <0.001, respectively, and such values remained significantly improved after ECMO, p=0.004 and 0.001 and <0.001, respectively. The mean time of ventilation after decannulation until extubation was 175±145.66 hours and the median time to intensive care unit discharge after decannulation was 234±110.30 hours. All 16 patients survived without neurological sequelae. Conclusions: ECMO could provide adjunctive pulmonary support for intubated asthmatic patients who remain severely acidotic and hypercarbic despite aggressive conventional therapy. ECMO should be considered as an early treatment in patients with status asthmaticus whose gas exchange cannot be satisfactorily maintained by conventional therapy for providing adequate gas change and preventing lung injury from the ventilation.